PDSS2‐Del2, a new variant of PDSS2, promotes tumor cell metastasis and angiogenesis in hepatocellular carcinoma via activating NF‐κB - Zeng, Tingting (Mol Oncol, 2020)
Hepatocellular carcinoma (HCC) is among the leading causes of cancer‐related mortality worldwide. Our previous study identified a novel alternative splicing variant of prenyl diphosphate synthase subunit 2 (PDSS2) in HCC characterized by a deletion of exon 2, named PDSS2‐Del2, which is devoid of the tumor‐suppressive function of full‐length PDSS2 (PDSS2‐FL). To better understand the clinical significance of PDSS2‐Del2, we performed a BaseScope™ assay on an HCC tissue microarray and found that positive staining for PDSS2‐Del2 predicted a worse overall survival in patients with HCC (P = 0.02). PDSS2‐Del2 levels correlated significantly with microvessel counts in HCC tumor tissues. Importantly, PDSS2‐Del2 overexpression functionally promoted HCC metastasis, as demonstrated by in vitro and in vivo migration assays. In vivo assays also demonstrated that PDSS2‐Del2 increased angiogenesis in xenografts. Furthermore, we discovered that elevated PDSS2‐Del2 expression in HCC tumor cells decreased fumarate levels and activated the canonical nuclear factor‐κB pathway. The epithelial‐to‐mesenchymal transition (EMT) and WNT/β‐catenin signaling pathways were also activated by overexpression. Dimethyl fumarate (DMF), a fumaric acid ester, effectively reduced the metastasis induced by PDSS2‐Del2 as observed with in vivo spleen‐liver metastasis animal experiments. DMF is a prescribed oral therapy for multiple sclerosis and it might be a potential treatment for metastasis of patients with HCC. Early clinical trials are needed to validate its potential in this context.